Organizational and Pedagogical Sonditions of the System of Professional Education of Primary School Teachers on the Bases of Folk Decorative- and Applied Arts - Galyna Buchkivska (Pedagogical Discourse, 2018)
The article attempts to analyze the influence of means of national culture, in particular folk decorative-applied arts, on the formation of a creative teacher, his or her aesthetic tastes and spiritual-moral values, ethnocultural self-identification and national consciousness.The organizational and pedagogical conditions have been determined that promote the effective realization of the pedagogical model of vocational training of future teachers of elementary school on the basis of folk decorative and applied art (formation of students' motivation for the knowledge of ethno-historical, spiritual and cultural heritage, embodied in works of folk decorative and applied arts, setting up of creative cultural and educational environment of professional preparation on the basis of folk arts and crafts; continuity of study of artistic and design-technological disciplines at all levels of training students in educational institutions of higher education; systematic involvement of students in extra-curricular educational work based on folk arts and crafts). The author selected traditional and innovative forms, methods and means of teaching, the introduction of which contributed to the deeper disclosure of the content of information and cognitive material, stimulation of creative activity, increased motivation of students to study folk arts and crafts, the use of its educational, cultural and educational potential in future professional activity.Develops methodical advice on creation of organizational and pedagogical conditions for efficient functioning of the system of future primary school teachers’ professional training on the basis of folk decorative and applied arts, as well as a tool for complex diagnosing of the level of readiness of students for creative artistic, labor and professional activity in elementary secondary school.